ANALISIS AGENCY PROBLEMS, CORPORATE GOVERNANCE, DAN STRUKTUR KEPEMILIKAN PADA PERUSAHAAN-PERUSAHAAN KEUANGAN DI INDONESIA - Ermawati, Wita Juwita (Optimum: Jurnal Ekonomi dan Pembangunan, 2012)
Implementation of corporate governance can not be separated from the agency problems that may occur in a company, and the companys ownership structure. Ownership structure of companies in Indonesia including financial firms are likely concentrated (closely held), so that the potential agency problems occur between majority/controlling shareholder and minority shareholders. For the banking sector, potential agency problems occur between owners and depositors (creditors) as well. How the corporate governance run will determine the agency problems that may occur. If there are high agency conflicts, so that corporate governance is not good and there are agency costs that may reduce the value of the company. Agency problems can be minimized through three mechanisms, namely an external mechanism, internal mechanism and market mechanism. Ideally, these three mechanisms can be well implemented. However, the more effective mechanism in ensuring good corporate governance is an external mechanism to oversight and strict law enforcement from regulator and the independent.